FACIES SUBDIVISION OF SHALLOW GRANITOIDS - Valuy G.A. (My University, 1988)
A characteristic feature of shallow granitoid rocks is graphic quartz-feldspar intergrowths, which are superb examples of a crystallized eutectic. The quartz content of these regular intergrowths is a sensitive indicator of the partial pressure of water, and thus might serve as an indicator of the facies to which intrusives belong. The author tried to decipher the conditions under which rocks of various granitoid facies had crystallized and separated within a single and, at first sight, homogeneous, granophyric granite intrusion. This study of the composition of graphic intergrowths and the ordering of feldspars which at first sight seem to be homogeneous, has revealed facies that differ in degree of fluid saturation and in emplacement depth. This is especially important in poorly exposed areas, where the geologist has to deal with separate, fragmentarily collected samples and is often unable to see how they are interrelated in space.